Boiler efficiency with mixed methane fuel gas calculation - abrar bin ridwan; Zaki anwar (Jurnal Polimesin, 2024)
A boiler is a pressurized vessel utilized for the production of high-temperature steam. An often-encountered problem in boiler systems is the inefficiency of the working system, especially in fire tube boilers where heat loss occurs in the steam and fuel systems, leading to a decrease in efficiency. Hence, it is imperative to compute the efficiency of fire tube boilers in order to comply with efficiency regulations in operational procedures in the field. This study utilizes indirect methods to calculate efficiency. The calculation results indicate that the boiler efficiency, determined using the indirect method, is 80.4%. The calculated result satisfies the minimum requirement for boiler efficiency, which is between 70-90%.